2022
DOI: 10.3390/insects13100962
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Vectors (Diptera: Culicidae) and Mosquito-Borne Diseases in North Africa

Abstract: Mosquitoes (Diptera: Culicidae) are of significant public health importance because of their ability to transmit major diseases to humans and animals, and are considered as the world’s most deadly arthropods. In recent decades, climate change and globalization have promoted mosquito-borne diseases’ (MBDs) geographic expansion to new areas, such as North African countries, where some of these MBDs were unusual or even unknown. In this review, we summarize the latest data on mosquito vector species distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 165 publications
0
7
0
Order By: Relevance
“…Finally, regarding the population's socioeconomic status, the study's findings suggest that the influence of socioeconomic status on MBDs did not show significant correlations in most studies [6]. This suggests that other factors, such as environmental conditions and healthcare access, could be more influential in determining the disease risk [13].…”
Section: Impacts Of Population Factors On Mbdmentioning
confidence: 82%
See 1 more Smart Citation
“…Finally, regarding the population's socioeconomic status, the study's findings suggest that the influence of socioeconomic status on MBDs did not show significant correlations in most studies [6]. This suggests that other factors, such as environmental conditions and healthcare access, could be more influential in determining the disease risk [13].…”
Section: Impacts Of Population Factors On Mbdmentioning
confidence: 82%
“…They found significant heterogeneity in published studies' distribution, quality, and quantity, which informs future research and surveillance priorities for the MBD in the MENA region. A more recent systematic review of MBD in North Africa was reported by Nebbak et al [6] in 2022. They found that 26 species are involved in circulating seven MBDs in North Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Among these species, the female Culex pipiens, specifically, is recognized as a vector for numerous pathogens that can cause fatal infectious diseases in humans and animals. [6][7][8][9][10][11] There are currently no effective preventive or curative methods for vector-borne diseases. The focus of strategies has been on controlling the vectors through the use of chemical insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…Among blood-sucking insects, mosquitoes (Diptera: Culicidae) are the most well-known class of vectors of pathogens causing serious diseases in humans and animals [ 1 , 2 ]. To date, 26 mosquito species have been identified as disease vectors, 8 of which belong to the Culex genus [ 2 , 3 , 4 ]. Culex pipiens L. (Diptera: Culicidae) is one of the most abundant Culex spp.…”
Section: Introductionmentioning
confidence: 99%
“…Culex pipiens L. (Diptera: Culicidae) is one of the most abundant Culex spp. in Europe and a major vector of several diseases with medical and veterinary importance [ 3 , 4 , 5 , 6 ]. Culex pipiens has been linked to the transmission of the major cause of lymphatic filariasis, Wuchereria bancrofti , and viral diseases including Rift Valley fever, St. Louis encephalitis, and the Sindbis and West Nile viruses [ 2 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%